2022
DOI: 10.1212/nxi.0000000000001136
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Dysmetabolism Are Dynamic Markers of Clinical Disability and Course in Anti-LGI1 Encephalitis

Abstract: Background and ObjectivesThis [18F]fluorodeoxyglucose (FDG) PET study evaluates the accuracy of semiquantitative measurement of putaminal hypermetabolism in identifying anti–leucine-rich, glioma–inactivated-1 (LGI1) protein autoimmune encephalitis (AE). In addition, the extent of brain dysmetabolism, their association with clinical outcomes, and longitudinal metabolic changes after immunotherapy in LGI1-AE are examined.MethodsFDG-PET scans from 49 age-matched and sex-matched subjects (13 in LGI1-AE group, 15 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 45 publications
4
39
1
Order By: Relevance
“…In this study, we investigated the anti-LGI1 AE metabolic pattern and identified hypermetabolism in the cerebellum, bilateral caudate nucleus, putamen, hippocampus and left Rolandic area, as well as hypometabolism in the left mPFC, in line with previous findings [13,25]. Previous semi-quantitative research showed hypermetabolism in the mesial temporal lobe structures and subcortical structures [26] or an increased metabolic ratio of putamen/global brain, putamen/thalamus and putamen/midbrain [27]. We applied voxel-based statistical t maps in a larger sample size to further validate the hypermetabolism in the above brain regions.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we investigated the anti-LGI1 AE metabolic pattern and identified hypermetabolism in the cerebellum, bilateral caudate nucleus, putamen, hippocampus and left Rolandic area, as well as hypometabolism in the left mPFC, in line with previous findings [13,25]. Previous semi-quantitative research showed hypermetabolism in the mesial temporal lobe structures and subcortical structures [26] or an increased metabolic ratio of putamen/global brain, putamen/thalamus and putamen/midbrain [27]. We applied voxel-based statistical t maps in a larger sample size to further validate the hypermetabolism in the above brain regions.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are consistent with previous studies about patients with anti-LGI1 encephalitis ( 6 , 28 , 29 ), suggesting that anti-LGI1 encephalitis is closely related to the metabolic abnormality in the medial temporal lobe and the basal ganglia. A recent study ( 7 ) also found that patients with anti-LGI1 encephalitis presented hypermetabolism in the medial temporal lobe and the basal ganglia (i.e., including the putamen and the caudate), consistent with the findings of the present study. However, some other brain regions showing metabolic abnormalities in the study ( 7 ) (e.g., angular gyrus, olfactory, and pons) were observed as normal regions in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study ( 7 ) also found that patients with anti-LGI1 encephalitis presented hypermetabolism in the medial temporal lobe and the basal ganglia (i.e., including the putamen and the caudate), consistent with the findings of the present study. However, some other brain regions showing metabolic abnormalities in the study ( 7 ) (e.g., angular gyrus, olfactory, and pons) were observed as normal regions in the present study. It should be noted that, in the study ( 7 ), the mean of standardized uptake values across the regions of interest was used to measure the metabolic abnormalities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations